Growth, Transformation and their Driving Forces of Kaysonphomvihan City: https://doi.org/10.69692/SUJMRD1001171 - SENGONKEO, Luangphasy; CHITPANYA, Soukanh; VENVONGTHONG, Phonguen; INTHAVONG, Daohieng; SIHAVONG, Saikhim; LASSAPHETH, Viengsavnah (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The city of Kaysonphomvihan is a city with an important strategic location in the central part of the Lao PDR. It has the East-West Economic Corridor (EWEC), the Savannakhet-Seno Special Economic Zone through it and the 13th North Road which is the national highway that cuts through from the north to the south. In the city, there is the Xeno Special Economic Zone, the bridge over the Mekong River which is the potential for the economic development of the city, thus making the city have population growth, economic growth and physical growth of the city, in the research study the growth, change and driving force in the development of Kaysonphomvihan city from 2005 to 2020. The city of Kaysonphomvihan, which will see the population growth during 2005-2020, in which in 2005 there were 112,915 people and in 2020 there was a population of 178,893 people, an increase of 65,978 people, which is 36.88 percent. Economic growth GDP per capita (USD) since 2005-2020, in which 2005 was 608 dollars, 2020 is 2,466 dollars, an increase of 1.858 dollars, which is 75.34 percent. The growth of the built area can be seen that in 2005 there is a built area of ​​432 hectares, in 2020 there is a built area of ​​865 hectares, an increase of 433 hectares, which is 50.06 percent. Throughout the period of 2005-2020, it can be seen that the city of Kaysonphomvihan has growth in the population, economy, physical of the city and has many driving forces that are the driving force in urban development from time to time.In this study, it is to be a guide in the planning, control and development of the city of Kaysonphomvihan to be sustainable.